Hazardous air pollutants in transmission pipeline natural gas: an analytic assessment. (1st October 2022) - Nordgaard, Curtis L; Jaeger, Jessie M; Goldman, Jackson S W; Shonkoff, Seth B C; Michanowicz, Drew R
Abstract: Natural gas production occurs in specific regions of the US, after which it is processed and transported via an interconnected network of high-pressure interstate pipelines. While the presence of hazardous air pollutants (HAPs) in unprocessed, upstream natural gas has been documented, little has been published on their presence in the midstream natural gas supply. We systematically evaluated publicly available, industry-disclosed HAP composition data sourced from Federal Energy Regulatory Commission (FERC) natural gas infrastructure applications submitted between 2017 and 2020. Natural gas composition data from these filings represent approximately 45% of the US onshore natural gas transmission system by pipeline mileage. Given that reporting natural gas HAP composition data is not required by FERC, only 49% of approved expansion projects disclosed natural gas HAP composition data. Of those applications that disclosed composition data, HAP concentrations were typically reported as higher for separator flash gas and condensate tank vapor compared to liquefied natural gas and transmission-grade natural gas, with mean benzene concentrations of 1106, 7050, 77, and 37 ppm respectively. We also identified one pipeline operator that reports real-time HAP concentrations for its natural gas at five pipeline interconnection points. Similar to the FERC applications, this operator reported benzene, toluene, ethylbenzene, xylenes and hydrogen sulfide as present in transmission pipeline natural gas. Notably, mercury was also reported as detectable in 14% of real-time natural gas measurements but was not reported in any FERC applications. Given that transmission infrastructure releases natural gas during uncontrolled leaks and loss of containment events as well as during routine operations (e.g. blowouts and compressor station blowdowns), these gas composition data may serve as a critical component of air quality and health-focused evaluations of natural gas releases.